If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = 3(-1) + -9 Multiply 3 * -1 Y = -3 + -9 Combine like terms: -3 + -9 = -12 Y = -12 Solving Y = -12 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = -12
| 4x^2+14x+20=0 | | -22-5.1=5+6(5.1)+9 | | 7x+9-5x-59=-100 | | Y=3(1)-9 | | -30-6=18 | | 6y-4=4x+10 | | -13-4b=1-6b | | 0.5x+8=20 | | 2a-2b=-10 | | 4(-1+2x)=76 | | -4x-7=-3x-2 | | w=95+28 | | 3k-5=-26 | | .2t+14.7=3.1 | | 5x^2+10=-50 | | (b+25)+3b=435 | | 1+2x+5y=12 | | .25+7.5=12.75 | | 8(x+3)+5=-35 | | -8k+ar=r-5y | | p=lrt(t) | | .7x+x=952 | | -164=-2-6(-6p+3) | | -100y+30=120+90 | | 28-5x=16+7x | | -19n-20=20-14n-13n | | 1a+4-8a=-10 | | 5(5-6x)=-125 | | -4+2c=0 | | (x-1)squared=16 | | -3x-24+2x+13=-3 | | -4u^2-17u-15= |